Transjugular Liver Biopsy - Behrens, George; Ferral, Hector (Seminars in Interventional Radiology, 2012)
Liver biopsy is considered the gold standard for the evaluation of acute and chronic liver disorders. Transjugular liver biopsy (TJLB) was described by Dotter in 1964 and clinically performed for the first time by Hanafee in 1967. TJLB consists of obtaining liver tissue through a rigid cannula introduced into one of the hepatic veins, typically using jugular venous access. The quality of the TJLB specimens has improved so much that the samples obtained by this method are comparable with those obtained with the percutaneous technique. TJLB is indicated for patients with coagulopathy, ascites, peliosis hepatis, morbid obesity, liver transplant, or in patients undergoing a transjugular intrahepatic portosystemic shunt procedure. The technical success rate for a TJLB procedure ranges from 87 to 97%. Sample fragmentation has been reported in 14 to 25% of the TJLB samples. The complication rates are low and range between 1.3% and 6.5%. The purpose of this article is to provide a review of the fundamental aspects of the TJLB procedure, including technique, indications, contraindications, results, and complications.
Keywords: liver biopsy; transjugular; interventional; image-guided